Genre analysis of the literature review section in hospitality and management research articles - Rafik-Galea, Shameem; De Mello, Geraldine; Arumugam, Nalini (Universiti Putra Malaysia Press, 2013)
Writing an effective literature review is not an easy task for novice writers of research articles, who are oftentimes unaware of the exact functions and purpose of this section; they are often unsuccessful in establishing the necessary connection between what has already been reviewed and the proposed research. This paper discusses the rhetorical patterns of the literature review (LR) section of Hospitality and Management (HM) research articles (RAs) from the perspective of genre analysis using the move structures as posited by Swales (2004). Twenty literature reviews from research articles in the Hospitality and Management discipline were analyzed to determine the move structure of the LR section. A moves analysis was carried out to identify the main moves and steps in the LR section. The analysis indicates that the LR sections display cyclical move patterns that show the presence of the 3 moves and their respective steps as postulated in Swales (2004) revised CARS model, but with some variations. The findings show that the LR section has Move 1 as an obligatory step and that HM RA writers favour making general statements about current situations as a beginning strategy. The findings further show that Move 2 Step 1B, ‘Adding to what is known’, is prevalent in the LR section because the writers will go on to contribute to the existing field of research by adding other research findings that are deemed necessary. Another outcome is that only Move 3-Step 1 is prevalent while the other 6 steps are either not found at all or are present in only a few of the samples.